The application of volumometry as an indication criterion in blow-out fractures - Kovar, Daniel; Holy, Richard; Voldrich, Zdenek; Voska, Pavel; Lestak, Jan; Astl, Jaromir (Biomedical papers, 2018)
Backgroung and Aim. This work builds on our publication on the subject of creating a mathematical model for calculating the volume of proplaped soft tissue of the orbit in blow-out fractures, which aids us greatly in our choice of the most effective treatment immediately post-accident. Patients and Methods: In this prospective study (2014 - 2016) we treated 29 patients with blow-out fractures. 18 (62%) were treated conservatively and in 11 (38%) we proceeded surgically. We decided whether surgical or non-surgical therapy was appropriate on the basis of clinical ENT, eye examination and the total volume of prolapsed orbital soft tissue. All procedures were perfomed by the same operating team with a uniform subciliary approach and using PMR splints adapted to the correct size and shape. Results: On the basis of the mathematical model we reassessed findings in 2 patients: in one we decided against a surgical solution and in the other a surgical approach was indicated. All 18 patients treated conservatively, fully recovered and are free of diplopia. The 11 operated patients are also free of diplopia, only 1 patient (3%) displays clinically insignificant postoperative diplopia in extreme posisitons when looking upwards. Conclusion: With proper selection of the optimal treatment, the rate of complete disappearance of diplopia and fully preserved motility of the eyeball ranges from 91 to 97%. Surgical treatment of orbital floor fractures is important, mainly to minimise persistent post-traumatic diplopia which significantly reduces a patient's quality of life.
Keywords: blow-out fractures; volumometry; diplopia; CT-assisted surgery